Dynamic control of the permanent magnet assisted reluctance synchronous machine with constant current angle - De Kock, Hugo Werner (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2006.